Enhancing of teaching and learning through constructive alignment - G. E. Dames (Acta Theologica)
This article elucidates issues about practical knowledge/deep learning on the current teaching and learning preaching practices in the Department of Practical Theology at the Faculty of Theology of the University of the Free State. The action learning and action research methodology is applied. Growing evidence indicates that there is a disjunction between the level of student competencies and incongruent teaching practices in the Faculty. Failure in the operationalization of both an interdisciplinary and a constructive alignment approach is at the core of surface learning. It appears that former and current students find it difficult to align their studies and to adapt to an unfamiliar, diverse, pluralistic and complex postmodern society. We teach content and assess students on the basis of what they know. The content does not relate to students’ own experiences or the broader issues in society. We are talking about a change that is deeper than surface alterations to the syllabus or to classroom teaching techniques. We are considering a radically different way of framing the ministry of preaching and of viewing the task of those who seek to learn and to teach preaching.